Retrieval of allocentric spatial memories is preserved up to thirty days and does not require higher brain metabolic demands - Zorzo, Candela; Arias, Jorge L.; Méndez, Marta (Neurobiology of learning and memory, 2020)
Spatial orientation is a cognitive ability that is indispensable for survival. Several visual distal cues present in the context can be integrated, establishing a cognitive map. Although there is cumulative evidence about the neural substrate involved in spatial memory acquisition, the brain networks mediating the processes involved in the retrieval of allocentric spatial memories have been studied less. Here, we aimed to explore the role of neuronal oxidative metabolism in the retrieval of allocentric spatial memories through cytochrome c oxidase (CCO) histochemistry seven, 15, 30, 45, and 60 days after task acquisition. Our behavioural results show that spatial memory retrieval in male and female rats is preserved seven, 15, and 30 days post-acquisition, but there is forgetfulness after this time, with subjects not being able to remember the position of the hidden platform after 45 and 60 dfearays. Regarding the study of male brain metabolism, we observed reduced CCO activity in the medial prefrontal cortex, the parietal, retrosplenial, rhinal cortex, and the hippocampal regions in all the groups that failed to solve the task. Similar results were found for female brain oxidative metabolism, in addition to certain differences between succefearssful-retrieval female groups. In conclusion, our work adds information about the behavioural retrieval of an allocentric spatial reference task, suggesting that recovering spatial information seven, 15, and 30days after acquisition is a simple task that does not require a high metabolic demand, in both male and female rats.